Reduction of the Structural Iron in Montmorillonite by Electron Transfer from Catechol and its Derivatives - Jasim HASSEN (Turkish Chemical Society, 2021)
The structural Fe(III) in montmorillonite (MMT) clay has been reduced using catechol and its derivatives. It was found that the reduction process is pH-dependent and also depends on the ring substituents. If the catecholic ring has electron-donating substituents, reduction happens at high pH; if the catecholic ring has electron-withdrawing substituents, no reduction occurs. The process involves electron transfer from the hydroxy groups on the compounds to the active site at the iron atoms within the MMT lattice. This site acts as an electron acceptor (Lewis acid). Heat treatment of the reduced sample at 100-300 oC showed an enhancement of the Fe2+/Fe3+ ratio, which is attributed to an increase in the proportion of radicalic formation induced by dehydration. The MMT sample was added to the solutions of the catecholic compound and the slurries were stirred for 24 hours in order to reach equilibrium, then filtered, washed, and air-dried. The reactions were monitored using Mössbauer spectroscopy, x-ray powder diffraction, differential thermal analysis, electron spin resonance, infrared, and total surface area determination.